2009
DOI: 10.1097/wnn.0b013e3181a72248
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Mercury Exposure, Breastfeeding and Neurodevelopment During the First 5 Years

Abstract: Until there is more refined approach to recognize children sensitive to Hg exposure, and in situations of uncertainty (EtHg exposure), the neurodevelopment benefit of breastfeeding should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 26 publications
0
40
0
1
Order By: Relevance
“…In the past, studies advised against breast feeding for a long period in fishing communities (Grandjean et al, 1994). At present, the benefits of breast feeding in terms of the neurodevelopment of children living in stressful environments are generally considered to outweigh the risks of mercury poisoning (Jensen et al, 2005, Marques et al, 2009. However, in this study, women breast-fed their children for a long time (mean age of weaning: 16.8 ± 6.5 months (Beneficeet al, 2006)), and could be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, studies advised against breast feeding for a long period in fishing communities (Grandjean et al, 1994). At present, the benefits of breast feeding in terms of the neurodevelopment of children living in stressful environments are generally considered to outweigh the risks of mercury poisoning (Jensen et al, 2005, Marques et al, 2009. However, in this study, women breast-fed their children for a long time (mean age of weaning: 16.8 ± 6.5 months (Beneficeet al, 2006)), and could be an issue.…”
Section: Discussionmentioning
confidence: 99%
“…In French Guiana, these vaccines are available free of thimerosal. However, breast-fed children do overcome sensitivity to early Hg exposure (which also includes vaccine ethylmercury) as measured by neurobehavioural tests at 5 years of age; (45) the effects of breast-feeding on improved performance of neurobehavioural tests have been established and partly attributed to high concentrations of PUFA (46) . Furthermore, comparing the high fish consumption of subsistence riverine children (Western Amazon) with those who rarely ate fish, a striking difference in HHg (fiftyeight times) was seen, but no significant differences in the results of neurocognitive tests (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Examinations on Amazonian population revealed no clear effects, however the validity of results are restricted due to methodological deficiencies such as insufficient information on prenatal exposure (Chevrier et al, 2009) and a relevant percentage of children with vaccination with thiomersalcontaining preparations (Dórea, 2007;Marques et al, 2007;Marques et al, 2008;Marques et al, 2009;Marques et al, 2011).…”
Section: Study Locationmentioning
confidence: 97%
“…However, almost half of these children had been vaccinated with thimerosal-containing preparations, so that observed effects could not only be attributed to MeHg intake by fish (Dórea, 2007;Marques et al, 2008;Marques et al, 2009;Marques et al, 2011 The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Amazonian Regionmentioning
confidence: 99%